2020
DOI: 10.1155/2020/8817948
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome and Its Determinants among Patients Admitted to Stroke Unit of Jimma University Medical Center, Southwest Ethiopia

Abstract: Background. Stroke is a public health problem in Ethiopia. Despite the high prevalence of stroke in Ethiopia, there is a paucity of data with regard to drug treatment, treatment outcome, and risk factors of poor treatment outcome of stroke. Hence, this study is aimed at assessing treatment outcome and its determinants among patients admitted to stroke unit of Jimma University Medical Center (JUMC). Methods. A two-year hospital-based retrospective cross-sectional study was employed to analyze the medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The most commonly prescribed medicines at HFSUH are statins (59.3%), antihypertensive therapy (57.9%), and aspirin (56.6%), The findings are consistent with research conducted in southwestern Ethiopia (Zewudie et al, 2020). However, these numbers are lower than that in a study conducted on the prescription pattern of drugs in stroke patients in India (Abbasi and Ali, 2012).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most commonly prescribed medicines at HFSUH are statins (59.3%), antihypertensive therapy (57.9%), and aspirin (56.6%), The findings are consistent with research conducted in southwestern Ethiopia (Zewudie et al, 2020). However, these numbers are lower than that in a study conducted on the prescription pattern of drugs in stroke patients in India (Abbasi and Ali, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…A good GCS assessment is described as mild brain injury/alert (GCS score of 13-15) or severe brain injury/drowsy (GCS score of 9-12). If the patient has serious brain injury/unconsciousness, a GCS score ≤8 is considered poor (Zewudie et al, 2020). For this study purpose, we classified GCS scores in two groups: <8 and >8.…”
Section: Operational Definitionsmentioning
confidence: 99%
“…A prospective study also reported 57.1% incidence of ischemic and 34.5% hemorrhagic stroke in Ethiopia [ 10 ]. Studies have shown that about two-thirds of hospitalized stroke patients in this country have poor treatment outcomes [ 11 ] and 18% die during hospitalization [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mortality and morbidity rates of stroke are still high. The outcome of stroke treatment depends on the speed of receiving appropriate treatment, which includes the time to receive intravenous thrombolysis or mechanical thrombectomy in ischemic stroke [2,3], or emergency surgery in hemorrhagic stroke [4]. Delayed prehospital time is an important factor that in uences treatment outcome in stroke [5].…”
Section: Introductionmentioning
confidence: 99%